Fansubbing and Professional Dubbing in Comic Movies: A Case Study of Taboo Renditions in Deadpool and The Interview - Jahandideh, Mohammad Hadi; Athari, Saeideh (LANGUAGE ART, 2021)
As a field of study, translation deals with rendering one language into another considering their linguistic features and cultural characteristics. ‘Fansubbing’ and ‘Professional Dubbing’ have drawn the researchers’ attentions and they have begun to investigate these versions of translation. This essay aims at exploring the differences between taboo renditions in professionally-produced and fanproduced subtitles of the selected comedies, Deadpool and The Interview. They are categorized based on Hashemian, Hosseini, and Mirzaei’s (2019) model. It classifies the strategies of translating taboo words into four main groups: ‘Taboo to Taboo’, ‘Taboo to Non-taboo’, ‘Euphemism’, and ‘Deletion’. In ‘Professional Dubbing’ version of these comedies, ‘Taboo to Non-taboo’ with the frequency of 46.7% was the topmost applied strategy in the rendition of the taboo words. In Fansubbing version, the strategy of ‘Taboo to Taboo’ was the most common one with 48.7% frequency. Analysis of Chi-square results considering p <0.05 indicates a meaningful difference between fansubbing and professional dubbing versions of these two movies.